1975
DOI: 10.1007/bf01911636
|View full text |Cite
|
Sign up to set email alerts
|

Thermogravimetric study of the effect of the chemical structure of polyimides on their thermal stability

Abstract: Thermogravimetry of polyimides based on dianhydrides of pyromellitic, diphenyland diphenyloxidetetracarboxylic acids and a series of diamines has been used to determine their temperature characteristics and calculate their activation energies. The dependence of the thermal stability of the polyimides on the structure of their diamine component was established. It was shown that the effect of the thermal stability of the polyimides progressively weakens with the increase in the rigidity of their chemical struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1976
1976
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…On the basis of T 10 , the polyimides had as high thermal stability as the polyimide from p-phenylene diamine and 3,3 ,4,4 -biphenyltetracarboxylic dianhydride, which was one of the most thermally stable polymer in the aromatic polyimides. 10 DSC curves of polyimides VIIIa, VIIIc, VIIId, and VIIIe showed glass transition temperature(T g ) around 230-265 • C followed by exothermic peaks (T c ) around 325-450 • C, above T g s. T g was essentially comparable to that of the previously reported polyimides prepared from 3,3 ,4,4 -p-quarterphenyltetracarboxylic dianhydride (m = 2) and 3,3 , 4,4 -p-sexiphenyltetracarboxylic dianhydride (m = 4), 6 at 235 • C and 233 • C, respectively, and did not undergo obvious transition due to crystallinity. This may be explained by the low rotational energy barrier around the ether linkages.…”
Section: Polymer Propertiesmentioning
confidence: 99%
“…On the basis of T 10 , the polyimides had as high thermal stability as the polyimide from p-phenylene diamine and 3,3 ,4,4 -biphenyltetracarboxylic dianhydride, which was one of the most thermally stable polymer in the aromatic polyimides. 10 DSC curves of polyimides VIIIa, VIIIc, VIIId, and VIIIe showed glass transition temperature(T g ) around 230-265 • C followed by exothermic peaks (T c ) around 325-450 • C, above T g s. T g was essentially comparable to that of the previously reported polyimides prepared from 3,3 ,4,4 -p-quarterphenyltetracarboxylic dianhydride (m = 2) and 3,3 , 4,4 -p-sexiphenyltetracarboxylic dianhydride (m = 4), 6 at 235 • C and 233 • C, respectively, and did not undergo obvious transition due to crystallinity. This may be explained by the low rotational energy barrier around the ether linkages.…”
Section: Polymer Propertiesmentioning
confidence: 99%
“…The most frequently used criteria are: tee temperature of the beginning of mass loss, the temperature of a definite mass loss (5 -50 ~), or inversely the mass loss corresponding to a certain temperature level (100-400~ This conclusion is confirmed, for instance, in the recent work of Sazanov and Koton [7]. The most frequently used criteria are: tee temperature of the beginning of mass loss, the temperature of a definite mass loss (5 -50 ~), or inversely the mass loss corresponding to a certain temperature level (100-400~ This conclusion is confirmed, for instance, in the recent work of Sazanov and Koton [7].…”
Section: Polymers Investigated By Ta Methodsmentioning
confidence: 82%
“…After the removal of easily volatile materials (losses up to 2 f 1.5%), the weight of the polymer is stabilized to TO and suddenly starts dropping due to an acceleration of the polymer chain breaking-down process. Koton et al [ 17,181 have observed that the structure of the diamine monomer affects the thermal stability. Various polyimides having different diamine components and a similar dianhydride component have been arranged in Table 5 in the order of thermal stability depending on the value of TO obtained.…”
Section: R E S U L T S a N D Discussionmentioning
confidence: 99%